Strategic Factors that Influence the Decision to Purchase Running Sportswear in Indonesia - Kairupan, Daniel Joel Immanuel (KINERJA, 2025)
Based on the National Survey of the Central Statistics Agency (Susenas BPS), running is the majority sport preferred by 41.45% of respondents. Interest in running as a sporting activity continues to increase in society, creating an atmosphere supporting the running community's growth. Social aspects, health, and lifestyle trends are several factors that influence this development. Based on several previous studies, several of these things affect the decision to purchase running sportswear. So, this research examines the purchasing decision of running sportswear with a sample of running enthusiasts in Indonesia. The respondents of this research are running enthusiasts in Indonesia. Data collection was carried out by distributing questionnaires online. The statistical tool used is Smart Partial Least Square (SmartPLS 3.0). The results show that purchase decisions are influenced by several factors, namely reference groups, lifestyle, and consumer preferences. The results obtained can be used by running sportswear companies to pay more attention to marketing strategies by always adapting to the dynamics of the times, including understanding market trends, changes in consumer behavior, and new technologies that may impact marketing strategies.